1984
DOI: 10.1002/1097-0142(19840301)53:5<1115::aid-cncr2820530517>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Necrotizing myelopathy associated with malignancy. A clinicopathologic study of two cases and literature review

Abstract: Two cancer patients had extensive spinal cord necrosis at necropsy. One had carcinoma of the breast and the other, carcinoma of the lung. Case 1 was treated by mastectomy, systemic chemotherapy and cranial irradiation, where as Case 2 received local irradiation to the right upper chest and right supraclavicular zone. In both cases, the spinal cord necrosis affected grey and white matter along most of its extent. Neither local nor systemic causes to explain the spinal cord lesion were disclosed at necropsy. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1
2

Year Published

1986
1986
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(19 citation statements)
references
References 21 publications
(1 reference statement)
0
16
1
2
Order By: Relevance
“…81 A review of the English literature by Ojeda et al revealed 22 cases of paraneoplastic necrotizing myelopathy. 92 Out of them, six were associated with lymphoma. [92][93][94][95] Serum or CSF may show onconeural antibodies such as CV2/CRMP5 and amphyphysin in solid tumors.…”
Section: Neurological Paraneoplastic Phenomenamentioning
confidence: 99%
See 1 more Smart Citation
“…81 A review of the English literature by Ojeda et al revealed 22 cases of paraneoplastic necrotizing myelopathy. 92 Out of them, six were associated with lymphoma. [92][93][94][95] Serum or CSF may show onconeural antibodies such as CV2/CRMP5 and amphyphysin in solid tumors.…”
Section: Neurological Paraneoplastic Phenomenamentioning
confidence: 99%
“…92 Out of them, six were associated with lymphoma. [92][93][94][95] Serum or CSF may show onconeural antibodies such as CV2/CRMP5 and amphyphysin in solid tumors. However, lymphomas are usually seronegative.…”
Section: Neurological Paraneoplastic Phenomenamentioning
confidence: 99%
“…In the latter, the possibility of a toxic or infectious origin was not completely ruled out. 74 The initial patients reported developed a severe and irreversible paraplegia, and postmortem studies of 2 cases revealed widespread spinal cord necrosis without prominent inflammatory infiltrates or vasculitis (necrotizing myelopathy). 74 This type of myelopathy has been described in a few cases with HL and NHL.…”
Section: Paraneoplastic Myelopathymentioning
confidence: 99%
“…Subsequently, cases of otherwise unexplained necrotizing myelopathy were associated with a wide variety of malignancies, including prostate cancer (Nonne, 1903;Whiteley et al, 1979;Gray et al, 1980), lung cancer (Nonne, 1919;D'Antona, 1926;L'hermitte and Bussière de Robert, 1941;Mancall and Rosales, 1964;Ojeda, 1984;Glantz et al, 1994;Lins et al, 2003), leg sarcoma (Feindel, 1921), squamous cell skin cancer (Moersch and Kernohan, 1934), stomach cancer (Juba, 1938), thyroid cancer (Jaffe and Freeman, 1943;Kuroda et al, 1993), non-Hodgkin's lymphoma (Williams et al, 1962;Richter and Moore, 1968;Nishida and Ziegler, 1973;Whiteley et al, 1979;Gray et al, 1980;Grignani et al, 1992;Drach et al, 1996;Anderson and Borsaru, 2008), breast cancer (Mancall and Rosales, 1964;Sieben et al, 1981;Ojeda, 1984;Mueller et al, 2008), ovarian cancer (Case records of the Massachusetts General Hospital, 1976), leukemia (Reznik, 1979;Grisold et al, 1980;Gieron et al, 1987), Hodgkin's lymphoma (Lester et al, 1979;Dansey et al, 1988;Hughes et al, 1992), renal cell carcinoma (Handforth et al, 1983;Wilson et al, 1983), hepatocellular carcinoma (Misumi et al, 1988), multiple myeloma …”
Section: Paraneoplastic Myelitismentioning
confidence: 99%
“…In some cases there is involvement of the cerebellum (Renkawek and Kida, 1983;Ojeda, 1984), thalamus (Nishida and Ziegler, 1973), brainstem, mammillary bodies, and temporal lobe (Gieron et al, 1987), internal capsule (Richter and Moore, 1968), centrum semiovale (Ojeda, 1984), and parietal lobe (Whiteley et al, 1979;Gray et al, 1980). That necrosis is not restricted to the spinal cord implies that a common pathologic process afflicts multiple areas of the nervous system simultaneously.…”
Section: Pathologymentioning
confidence: 99%